Addressing potential impact of COVID-19 pandemic on physical and mental health of elite athletes - Mehrsafar, A. H.; Gazerani, P.; Zadeh, A. M.; Jaenes Sanchez, J. C. (Brain, Behavior, and Immunity, 2020)
In critical situations, health authorities and sport communities must identify their priorities and make plans to maintain athletes` health and athletic activities. Several aspects play an important role in prioritization and strategic planning, e.g., physical and mental health, distribution of resources, and short to long-term environmental considerations.